2022
DOI: 10.3390/s22083060
|View full text |Cite
|
Sign up to set email alerts
|

Anthropomorphic Robotic Eyes: Structural Design and Non-Verbal Communication Effectiveness

Abstract: This paper shows the structure of a mechanical system with 9 DOFs for driving robot eyes, as well as the system’s ability to produce facial expressions. It consists of three subsystems which enable the motion of the eyeballs, eyelids, and eyebrows independently to the rest of the face. Due to its structure, the mechanical system of the eyeballs is able to reproduce all of the motions human eyes are capable of, which is an important condition for the realization of binocular function of the artificial robot eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 192 publications
0
4
0
Order By: Relevance
“…In the process of online marketing, companies using anthropomorphic communication can compensate for the lack of presence in online consumption, reducing consumers' perception that brands are impersonal and inhuman, and enhancing customer happiness [20]. When consumers receive personalized marketing using anthropomorphic communication with low information sensitivity, they are more likely to regard personalized marketing as sharing between friends rather than having cold sales purposes, resulting in more positive feelings and reducing privacy concerns [21]. The use of anthropomorphism in advertising services could also weaken consumers' perception of the hidden motives of advertisers and reduce their suspicion of advertising information [5].…”
Section: Anthropomorphism and User Sentimentmentioning
confidence: 99%
“…In the process of online marketing, companies using anthropomorphic communication can compensate for the lack of presence in online consumption, reducing consumers' perception that brands are impersonal and inhuman, and enhancing customer happiness [20]. When consumers receive personalized marketing using anthropomorphic communication with low information sensitivity, they are more likely to regard personalized marketing as sharing between friends rather than having cold sales purposes, resulting in more positive feelings and reducing privacy concerns [21]. The use of anthropomorphism in advertising services could also weaken consumers' perception of the hidden motives of advertisers and reduce their suspicion of advertising information [5].…”
Section: Anthropomorphism and User Sentimentmentioning
confidence: 99%
“…From the above-mentioned problems resulting from traditional landmarks, in order to eliminate the problems where the number of landmarks produce insignificant characteristics, we propose an approach that has the ability to flexibly detect a number of significant upper facial landmarks without a fixed number and location of landmarks, as shown in Figure 6. As per Equation (7), our detected landmarks do not have to be located around the eyebrows, eyes, or nose. Our process does not require us to take all the pixels from the upper face.…”
Section: Input Features Type Limitationmentioning
confidence: 99%
“…Moreover, emotion recognition and face perception are highly associated with one another, and challenges are even more severe for the people who have a hearing disability and who mostly communicate through facial expressions, especially through the mouth. Emotion recognition is important because it can be applied to a vast number of applications, such as those in [2][3][4][5][6][7], for problem solving and are of exceptional value to both organizations and communities. For instance, facial emotion recognition applications have been produced to improve human-computer interaction [8].…”
Section: Introductionmentioning
confidence: 99%
“…They are the main medium of emotional expression and directly affect the user’s understanding and acceptance of the robot’s emotional state ( Chakraborty et al, 2021 ). Research has demonstrated that incorporating human-like eye expressions in emotional robots can substantially enhance the accuracy of emotion perception ( Penčić et al, 2022 ). Nevertheless, there are still constraints in using robot emotion expressions solely based on human-like eyes.…”
Section: Introductionmentioning
confidence: 99%